Regional trends of minimally invasive radical hysterectomy for cervical cancer and exploration of perioperative outcomes. (April 2022) - Holtzman, Sharonne; Chaoul, Jessica; Finkelstein, Mark; Kolev, Valentin; Zakashansky, Konstantin
Abstract: Introduction: Radical hysterectomy (RH) with bilateral pelvic lymph node dissection is the standard treatment for early stage cervical cancer which can be performed either by an abdominal or a minimally invasive (MIS) approach. In 2018, Ramirez et al. presented their randomized-controlled trial data which demonstrated that patients who were treated with minimally invasive surgical (MIS) radical hysterectomy (RH) had higher rates of locoregional disease recurrence and lower rates of overall survival when compared to patients treated with an abdominal approach. The objective of this study is to examine the trends in management of patients diagnosed with cervical cancer in New York State (NYS) and to analyze their perioperative outcomes. Methods: Using the Statewide Planning and Research Cooperative System (SPARCS) Database, patients undergoing RH for early stage cervical cancer in NYS between the years of 2007–2015 were identified and categorized based on surgical approach. Demographic information was collected and multivariable regression was conducted to assess the impact of hysterectomy approach on perioperative outcomes. Results: In NYS, 5575 patients were treated with RH for early stage cervical cancer with 3257 (58.4%) treated by abdominal RH and 2318 (41.6%) treated with MIS RH. Between the years of 2007 and 2015, patients diagnosed with cervical cancer treated with MIS RH increased from 25.7% to 48.3% respectively. Surgeons performing MIS RH were more likely to be younger (average age 47.1 vs 49.2, p < 0.001) and have less time elapsed from their fellowship graduation (20.37 vs 22.64 years, p < 0.001). Patients who saw high volume doctors (OR 1.95, CI 1.65–2.31) and were seen in high volume facilities (OR 1.40, CI 1.18–1.65) were more likely to undergo MIS RH compared to abdominal RH. Patients who underwent MIS RH were more likely to be discharged home as opposed to acute rehab or nursing facility, when compared to patients treated with abdominal RH (98.5 vs 94.2% p < 0.001). When analyzing perioperativce outcomes, patient undergoing MIS RH had a 85% decrease in length of hospital stay compared to abdominal RH, a 40% reduction in 30-day readmission rates, and a 10% reduction in hospital costs respectively. Discussion: In our study period, between the years of 2007 and 2015, the number of cervical cancer cases treated with MIS RH increased from 25.7% to 48.3%. MIS techniques led to a reduction in length of hospital stay, patient readmission rates, and hospital costs. Based on recent data from Ramirez et al., preliminary data demonstrated decrease in MIS RH for treatment of cervical cancer after presentation of the LACC trial and our data confirmed these reported trends in NYS. With this change in surgical practice, there will be associated changes in perioperative outcomes. Moreover, for patients diagnosed with cervical cancer with microscopic disease or previous treatment with an excisions procedure, MIS approach should be considered for improvement in perioperative outcomes as long as oncologic outcomes are not compromised. Highlights: The number of cervical cancer cases treated with MIS RH almost doubled between 2007 and 2015 in NYS. Minimally invasive techniques led to reduction of length of hospital stay, readmission rates, and hospital costs. Based on newly presented data reporting inferior oncological outcomes of MIS RH compared to the abdominal approach, many centers have again prioritized the abdominal surgical approach. We highlight that the potential reversal in surgical approach may have a significant impact on gynecologic oncology practice, affecting perioperative outcomes, healthcare costs, and surgical training.